Efficacy of acupuncture versus sham acupuncture on generalized anxiety disorder: a meta-analysis of randomized controlled trials - Jiang, Hongzhan; Ma, Ruiqing; Huang, Yaxin; Li, Xuejing; Hao, Yufang (Frontiers in Neurology, 2025)
ObjectiveThis meta-analysis aimed to evaluate the specific efficacy of acupuncture compared to sham acupuncture in the treatment of generalized anxiety disorder (GAD), beyond nonspecific or placebo effects.MethodsWe systematically searched PubMed, Web of Science, CNKI, WanFang, VIP, Cochrane Library, ClinicalTrials.gov, and EMBASE from inception to October 2025. Randomized controlled trials (RCTs) comparing acupuncture with sham acupuncture in adults diagnosed with GAD were included. Primary outcome was the Hamilton Anxiety Scale (HAMA), with secondary outcomes including Self-Rating Anxiety Scale (SAS), Generalized Anxiety Disorder 7-item scale (GAD-7), Pittsburgh Sleep Quality Index (PSQI), Self-Rating Depression Scale (SDS), cortisol (CORT), and adrenocorticotropic hormone (ACTH). Data were pooled using random- or fixed-effects models based on heterogeneity (I2). Risk of bias was assessed using the Cochrane tool, and evidence certainty was evaluated via GRADE.ResultsFourteen RCTs involving 968 participants were included. Acupuncture demonstrated significant reductions in HAMA [MD = −2.71, 95% CI (−4.17, −1.25), p = 0.0003], SAS [MD = −9.33, 95% CI (−16.29, −2.36), p = 0.009], GAD-7 [MD = −2.99, 95% CI (−5.52, −0.45), p = 0.02], PSQI [MD = −2.83, 95% CI (−5.37, −0.28), p = 0.03], and SDS [MD = −11.40, 95% CI (−19.89, −2.92), p = 0.008]. Small but significant effects were observed for CORT (SMD = −0.33, p = 0.007) and ACTH (MD = −3.18, p = 0.04). Heterogeneity was high for most outcomes. Evidence certainty was low to very low for patient-reported outcomes and moderate for biomarkers.ConclusionAcupuncture is more effective than sham acupuncture in alleviating anxiety symptoms and improving sleep and mood in patients with GAD, though effect sizes are modest and evidence certainty varies. These findings support acupuncture as a potential non-pharmacological option for GAD, yet further high-quality trials are needed to standardize protocols and clarify mechanisms.